Efektivitas Komunikasi Dakwah Melalui Radio - Surianor Surianor (Alhadharah: Jurnal Ilmu Dakwah, 2017)
The problems discussed in this paper is about the nature of dakwah and communication and point of contact between the two, the position of radio as a medium of communication to convey messages of dakwah, as well as the effectiveness of the delivery of dakwah messages through radio. This paper concludes, effective dakwah messages delivered via radio, supported by radio producer with the announcers who are capable of processing dakwah material efficiently and effectively, educative, sensitive, and entertaining. The message should be the needs of the listener, at a minimum be able to attract them. The language used should be thoroughly understood by the listener with sound quality that is clear and effective. Given public radio listeners cannot be limited, dakwah radio need to pay attention to diversity of listeners in terms of ethnicity, religion, race and class. The dakwah messages is inclusive, soothing and able to provide solutions to the problems of public life as a characteristic of Islam that rahmatan lil 'Alamin important to be used as broadcast. From here it is possible that dakwah over radio will be favored so as to encourage more people to accept and practice the teachings of Islam.Permasalahan yang dibahas dalam tulisan ini adalah mengenai hakikat dakwah dan komunikasi dan titik singgung antara keduanya, kedudukan radio sebagai media komunikasi untuk menyampaikan pesan dakwah, serta efektivitas penyampaian pesan dakwah melalui radio. Tulisan ini menyimpulkan, pesan-pesan dakwah efektif disampaikan melalui radio, dengan didukung produser radio bersama para penyiarnya yang mampu mengolah bahan siaran dakwah secara efisien dan efektif, mendidik, menyadarkan, sekaligus menghibur. Pesan tersebut harus menjadi kebutuhan pendengar, minimal mampu menarik minat mereka. Bahasa yang digunakan harus benar-benar dipahami oleh pendengar dengan kualitas suara yang jelas dan efektif. Mengingat masyarakat pendengar radio tidak bisa dibatasi, radio dakwah perlu memperhatikan keragaman pendengarnya baik di segi suku, agama, ras dan golongan. Pesan-pesan dakwah yang bersifat inklusif, menyejukkan hati dan mampu memberikan solusi terhadap problema kehidupan masyarakat sebagai ciri khas agama Islam yang rahmatan lil ’alamin penting untuk dijadikan bahan siaran. Dari sini tidak mustahil dakwah melalui radio akan disenangi sehingga mendorong orang untuk lebih menerima dan mengamalkan ajaran Islam.